Effects of internal rigid fixation on mandibular development in growing rabbits with mandibular fractures (2012)
Purpose: The aim of this research was to determine whether rigid internal fixation interferes with mandibular growth and development in growing New Zealand white rabbits with induced mandibular fractures. Materials and Methods: Ten 3-month-old New Zealand white rabbits were included in the study. Surgical fractures were performed in the right mandibular bodies of the 10 rabbits. These fractures were reduced with internal rigid fixation by use of a 1.0-mm titanium system, taking the contralateral left mandibular bodies as the control group. We obtained radiographs preoperatively and at 1, 2, and 3 months postoperatively. Predetermined cephalometric points were used to measure and compare jaw growth. The protocol was approved by the Bioethics Committee of Universidad El Bosque, Bogotá, Colombia. Results: There were no statistically significant differences between the experimental and control groups (P =.95). Mandibular growth in the studied rabbits was not affected by the use of internal rigid fixation. Conclusions: The use of internal rigid fixation for the treatment of induced mandibular fractures in growing rabbits did not alter the normal process of growth and development. The findings of this study should lead to investigations using larger samples and to long-term prospective follow-up studies of children who have undergone open reduction and internal rigid fixation.